THE SITUATION AT THE INSTITUTE OF ANATOMY, MEDICAL FACULTY, BRATISLAVA, SLOVAKIA - Zora Haviarova; Veronika Važanová (Asociación Argentina de Anatomía Clínica, 2023)
In the number of medical students and graduated medical doctors in past 5 years women prevail at our Medical Faculty. This should be due to quite difficult study and also  a further career. Among the teaching and research staff also women prevail- but teaching profession is more popular among the women than man.